Workplace safety, government workplace safety regulations, employee safety attitudes and employees’ productivity in manufacturing firms in kenya - Mwenda, Tetu Mutegi. (UoEm, 2023)
The manufacturing sector in Kenya has been experiencing workplace safety and productivity issues despite adopting safety programmes and laws regulating workplace safety. Extant studies have yet to examine the relationship between workplace safety and employees’ productivity. This study’s general objective was to determine workplace safety’s effect on employees’ productivity. The study was grounded on the domino, homeostasis, tip of the iceberg, and Rasmussen’s risk management theories. The study design was a cross-sectional survey guided by a positivist research philosophy. The target population was 853 manufacturing firms registered with the Kenya Association of Manufacturers. A sample of 234 firms distributed across the fourteen manufacturing sub-sectors was obtained using a statistical formula to ensure all sectors were represented. The sampled firms were then selected using a random sampling method. The target respondents were 234 heads of human resources in each sampled firm. The questionnaire was pre-tested in 24 manufacturing firms. The structured questionnaire reliability was checked using Cronbach’s alpha which revealed a correlation coefficient of 0.897. To describe profiles of the firms and research variables, means and standard deviations were used. Multiple regressions were used to analyze objectives. The study established that workplace safety has a statistically significant influence on employees’ productivity. Thus, each workplace safety construct; ergonomics, emergency management, safety training, and safety transfer statistically affects employees’ productive time, value-added, and accomplishment of tasks. In addition, the study found that workplace safety affected employee productivity regardless of the manufacturing sector. Moreover, the study determined that the level of implementation of government regulation has a significant moderating effect on the relationship between workplace safety and employees’ productivity. Further, it was established that employee safety attitude significantly intervened in the relationship between workplace safety and employees’ productivity. Finally, the study found that workplace safety, implementation of government workplace safety regulations, and employee safety attitude jointly affect employees’ productivity. The study recommended that firms that intend to improve their employees’ productivity should invest in adequate workplace safety, fully implement government safety regulations, and launch programmes that foster positive employee safety attitudes. This will enable employees to accomplish tasks better, add value and productive time. The study’s findings offer insight into the situational position of workplace safety, level of implementation of government workplace safety regulations, employee safety attitude, and employee productivity in manufacturing firms in Kenya, as well as managerial and epistemological insights for scholars in human resources management. The findings further expand existing theoretical frameworks; contribute to policy development and human resources management practices. The research had a few limitations; the selection of the study variables did not cover different psychological traits and personalities possessed by an employee, which led to varying safety attitudes and productivity. Future research should address these limitations by including additional psychological traits, personalities, and soft and hard human resources management approaches.
Thesis